Proceso de atención de enfermería en lactante menor con infección de vías urinarias. - Guerrero Vera, Olga María (2021)
The following clinical case is based on the analysis of the urinary tract infection diagnosed in a 2-month-old infant at the Martin Icaza General Hospital. The objective of this case study is to establish a care plan applying the Nursing Care Process (PAE) in the patient through the description of the medical history, health status, applied tests, identification of functional patterns. Urinary tract infection is one of the most common bacterial infections in childhood and, although the prognosis is favorable in most cases, recurrence of urinary sepsis can cause damage to the kidney parenchyma, triggering long-term complications local and systemic. It is important to identify risk factors and activate clinical suspicion to make an adequate diagnosis and apply early treatment, and thus reduce the probability of kidney damage. Symptoms of general illness and laboratory abnormalities can also be found in the absence of acute parenchymal lesions.